Analysis of serum Calcium, Magnesium, and Parathyroid Hormone in neonates delivered following preeclampsia treatment - Vahabi, S.; Zaman, M.; Farzan, B. (Cellular and Molecular Biology, 2016)
Due to the approximate clinical and biochemical manifestations of calcium and magnesium disturbances, with regard to the regulatory effects of parathyroid hormone (PTH), this present study is designed to analyze serum calcium (Ca), magnesium (Mg), and (PTH) at the time of birth, 24 hours afterwards in newborns after the mother has been treated with Mg-sulfate. We registered 86 term and preterm neonates (43 in each group) using simple census method delivered through vagina to preeclampsia pregnant women treated with Mg-sulfate immediately before birth in Khoramabad Asali Hospital, Iran. The first specimen was obtained from umbilical cord blood at birth, followed by the second sample of 2cc peripherally obtained from blood 24 hours after birth. The mean serum Mg level was higher than normal for both specimens in both term and preterm groups with no significant difference. The mean serum Ca level was higher in term group at both occasions, which turned out to be statistically significant (P<0.000) and (P=0.001) for the first and second specimens respectively. The mean PTH level was also in normal range for both groups at both times with no statistical significance. On the other hand, magnesium level showed a significant decline at 24 hours (P = 0.005) while PTH increased significantly (p<0.000) and (p=0.005) for term and preterm groups respectively. In contrast, Ca changes were not significantly different between the two specimens. Treatment with Mg-sulfate immediately before vaginal delivery increases Mg in both term and preterm neonates with no effect on Ca and PTH levels.